Sigi's Response to the Disaster Program: Nutrition, Sanitation, and Food Fulfillment - Hilda Carmitha Panjaitan; Theresia Pratiwi Elingsetyo Sanubari; Fiane de Fretes (Global Medical & Health Communication (GMHC), 2021)
The earthquake occurring in Indonesia caused various problems, especially the decreased degree of human health caused by insufficient food availability. It makes victims of natural disasters need assistance from government programs. One case of a natural disaster in 2018 was an earthquake in Central Sulawesi. Unfortunately, disaster survival has the challenge to continue their living caused by program absences from the government in post-disaster. This study aimed to explore disaster survival's resilience after one year of the earthquake disaster in Sidera village, Sigi regency, in response to government programs, especially nutrition, sanitation, and food fulfillment response. This research used mixed-method approaches with a cross-sectional design. Data collection was done with questionnaires, in-depth interviews, and anthropometric measurements. The study was conducted from February to April 2020 with 30 refugees in the temporary shelter in Sidera village as respondents. The study results found that people still need to initiate countermeasures related to sanitation and fulfillment of food. Government programs in health services produce good conditions related to normal nutritional status at the age of 5 years (40%), 5–18 years (100%), and 18 years (41%). The conclusion is that the government program is not sustainable, which makes the community still need to initiate countermeasures related to sanitation and food fulfillment. The program recommendations are to ensure clean water availability and guide the community to fulfill their food need. TANGGAPAN SIGI TERHADAP PROGRAM BENCANA: GIZI, SANITASI, DAN PEMENUHAN PANGANGempa bumi yang terjadi di Indonesia menyebabkan berbagai masalah, secara khusus penurunan derajat kesehatan manusia dikarenakan oleh ketersediaan pangan yang tidak tercukupi. Hal tersebut membuat korban bencana alam membutuhkan bantuan dari program pemerintah. Salah satu kasus bencana alam tahun 2018 adalah gempa bumi di Sulawesi Tengah. Namun, hingga pascabencana, korban bencana alam masih tinggal di pengungsian tanpa program. Tujuan penelitian ini adalah mengeksplorasi daya lenting pengungsi pasca-satu tahun bencana gempa bumi di Desa Sidera, Kabupaten Sigi sebagai tanggapan dari program pemerintah khususnya gizi, air bersih, dan pemenuhan pangan. Penelitian ini menggunakan pendekatan mixed-method dengan desain cross-sectional. Teknik pengumpulan data dilakukan melalui pengisian kuesioner, in depth interview, serta pengukuran antropometri. Penelitian dilakukan pada 30 responden yang merupakan pengungsi di hunian sementara (huntara) Desa Sidera. Penelitian dilakukan selama bulan Februari hingga April 2020. Hasil penelitian menemukan bahwa masyarakat masih perlu melakukan inisiasi penanggulangan terkait air bersih dan pemenuhan pangan. Program pemerintah terkait pelayanan kesehatan menghasilkan kondisi yang baik terkait status gizi normal pada usia ≤5 tahun (40%), 5–18 tahun (100%), dan ≥18 tahun (41%). Simpulan dari penelitian ini adalah program pemerintah tidak memiliki keberlanjutan, hal tersebut membuat masyarakat masih perlu melakukan inisiasi penanggulangan terkait air bersih dan pemenuhan pangan. Rekomendasi program yang dapat diberikan adalah ketersediaan air bersih serta pemantauan program dalam membimbing masyarakat agar dapat memenuhi kebutuhan pangan.